INDIVIDUO: Results from a patient-centered lifestyle intervention for obesity surgery candidates - Camolas, José (2018)
This manuscript is made available under a CC-BY-NC-ND 4.0 license - https://creativecommons.org/licenses/by-nc-nd/4.0/